Antibacterial, flame retardant, and physico‐chemical properties of cotton fabric graft copolymerized with a binary mixture of acrylonitrile and 4‐vinylpyridine. Issue 13 (30th January 2014) - Kaur, Inderjeet; Bhati, Pooja; Sharma, Bharti
ABSTRACT Modification of cotton fabric has been carried out through chemically induced graft copolymerization of binary mixture of acrylonitrile (AN) and 4‐vinyl pyridine (4‐VP) using ceric ammonium nitrate, (CAN) as initiator. Maximum percentage of grafting (151.28%) has been obtained at [4‐VP] = 0.376 mol L−1 and [AN] = 1.221 mol L−1, [CAN] = 0.0255 mol L−1 and [HNO3] = 0.9585 mol L−1 in 25mL of water at 70°C in 180 min. Post quarternization and phosphorylation reactions of the grey and grafted cotton fabrics have been carried out to study their antibacterial and flame retardant properties respectively. The fabrics have been characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). The physico‐chemical properties such as wettability, moisture regain, crease recovery and tensile strength of the grey and grafted cotton fabric have also been evaluated. The modified fabric has been shown to exhibit excellent antibacterial and flame retarding properties with improved physico‐chemical properties except for the mechanical properties. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40415.